Serological profile of buffalo (Bubalus bubalis) female calves vaccinated with standard brucella abortus strain 19 vaccine using rose Bengal, 2-mercaptoethanol and complement fixation tests - de Nardi Júnior, Geraldo; Jorge, André Mendes [UNESP]; Ribeiro, Márcio Garcia [UNESP] (My University, 2013)
The serological profiles of 21 female buffaloes vaccinated between 3 to 8 months of age using Brucella abortus strain 19 (S19) were evaluated by rose bengal (RBT), 2-mercaptoethanol (2ME) and complement fixation (CFT) tests. The serum strains were collected in day zero (day of vaccination), 15, 30, 45, 60th days and subsequently to each 30 months, until 720th day after vaccination. No animal showed reaction in day zero. In 15th day, above 95% of animals revealed reaction in all tests. The maximum levels of antibodies detected by the 2ME were found between 15 and 45th days after vaccination. Among 120 and 150 days after vaccination was observed decreased of reactions in all the tests. All the animals presented absence of reactions in CFT, RBT and 2ME tests at 270, 300 and 360 days after vaccination, respectively. Our finding highlighted early response in CFT compared than other conventional agglutination tests. None of animals presented oscillation of titers or reactions in any test after 360 day of study, which enables the use of CFT, RBT and 2ME after this period without interference of antibodies from vaccine origin using S19 between 3 to 8 months in buffalo heifers.
Keywords: Brucellosis; Buffalo; Serodiagnosis; Strain 19; Vaccination